2006
DOI: 10.1177/0018726706065370
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and the psychological contract: Structural holes, cohesive ties, and beliefs regarding employer obligations

Abstract: This study examined the relationship between employees' social network positions and their psychological contract beliefs. In particular, it investigated the relationship of employee advice and friendship ties with their employer's relational (long-term, non-monetizable), balanced (performance-related), and transactional (short-term, monetizable) obligations to them. Data obtained from a start-up research firm showed that employees brokering structural holes in the advice network believed the firm had greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 47 publications
(75 reference statements)
3
74
0
1
Order By: Relevance
“…Perceptions of social networks were seen to mitigate the negative effect of contract breach on turnover, in particular through social status and strong connectedness with the respective senior officers. The research confirmed the important link between PCB and employee social network positions (Ho et al, 2006).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…Perceptions of social networks were seen to mitigate the negative effect of contract breach on turnover, in particular through social status and strong connectedness with the respective senior officers. The research confirmed the important link between PCB and employee social network positions (Ho et al, 2006).…”
Section: Resultssupporting
confidence: 66%
“…There has only been limited research into the moderating effects of workplace social networks on turnover intention from a psychological contract perspective (Ho et al, 2006). Krackhardt (1992) noted that the strength of the emotional and behavioural reactions that follow a contract breach might be moderated by an individual's network within the organisation.…”
Section: Moderating Role Of Social Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, the study of how people allocate their time among different activities, such as work or leisure, has been a subject of economic studies (Becker 1965;Ghez and Becker 1975;Linder 1960). Here, however, we are interested in analyzing of how people allocate time and attention among one another, a topic that has been usually addressed from sociological and psychological perspectives (Dunbar 1992;Granovetter 1973;Southerton 1986;Wellman 2007;Winship 1978), aimed to understand how this dynamics might affect phenomena such as network cohesion (Ho et al 2006;Gargiulo and Benassi 2000), strategy and cooperation (Burt 1992;Seibert et al 2001) and organizational performance (Benner and Tushman 1999;March 1991).…”
Section: Social Strategies In Communication Networkmentioning
confidence: 99%